Penyuluhan Peran Kader Dalam Meningkatkan Literasi Kesehatan Masyarakat di Desa Cimanggu, Bandung Barat - Ditha Prasanti; Ikhsan Fuady (Universitas Mathla'ul Anwar Banten, 2017)
CULTIVATION OF CADRE ROLE IN IMPROVING COMMUNITY HEALTH LITERATION IN CIMANGGU VILLAGE OF BANDUNG BARAT DISTRICT. Community Service Activities has the objective to produce outcomes, namely: 1) Providing concrete knowledge and insight on the counseling of the role of cadres in improving public health literacy in the village Cimanggu, Bandung Barat District; 2) Provide an understanding of the importance of the role of cadres in improving the public health literacy in Cimanggu village, District of Bandung Barat. The method of PKM implementation conducted in this training activity is method of lecture method; Group discussion methods; and video playback methods. The conclusions of this PKM activity are: (1) As a benchmark for Kader members in Cimanggu village to be able to increase public health literacy for better village development; (2) Awakening PKM participants on the importance of the role of Cadres in improving public health literacy; (3) Increasing awareness of PKM participants on the importance of increasing public health literacy in order to support the successful development of Cimanggu village.